The Effect of Price on Firm Reputation - Luca, Michael; Reshef, Oren (Management Science, 2021)
Although a business’s reputation can affect its pricing, prices can also affect its reputation. To explore the effect of prices on reputation, we investigate daily data on menu prices and online ratings from a large rating and ordering platform. We find that a price increase of 1% leads to a decrease of 3%–5% in the average rating. Consistent with this, the overall distribution of ratings for cheaper restaurants is similar to that of more expensive restaurants. Finally, these effects do not seem to be driven by consumer retaliation against price changes but by changes in absolute price levels. This paper was accepted by Duncan Simester, marketing.